2017
DOI: 10.2147/jpr.s151370
|View full text |Cite
|
Sign up to set email alerts
|

Thermal camera as a pain monitor

Abstract: ObjectivesToday, many subjective methods are used to measure pain. Wong Baker and Hicks Facial Pain Scale is one of the most commonly used method. Clinicians grade pain according to the facial mimetic reaction of the patient. Unfortunately, there is no objective measure for monitoring pain. By using the same principle of the Wong Baker and Hicks Facial Pain Scale, in this study, we aimed to objectively measure pain by using a thermal camera to detect instant facial temperature changes.Materials and methodsThir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…We opted for a TI camera in this study to ascertain whether pain relief represents merely a diminution in pain perception or if physiological changes are concurrently occurring. The TI camera was chosen because it is non-intrusive and an effective tool for monitoring physical pain [71] [72].…”
Section: Hypothesis 1 (H1): Gillmore's Mind-body-emotion Health Hypot...mentioning
confidence: 99%
“…We opted for a TI camera in this study to ascertain whether pain relief represents merely a diminution in pain perception or if physiological changes are concurrently occurring. The TI camera was chosen because it is non-intrusive and an effective tool for monitoring physical pain [71] [72].…”
Section: Hypothesis 1 (H1): Gillmore's Mind-body-emotion Health Hypot...mentioning
confidence: 99%
“…Indeed, evidence of thermal changes in the lacrimal carunculae have been found to appear in response to noxious stimuli ( Kolosovas-Machuca et al, 2016 ). This research opens the door for using thermography as a non-invasive imaging modality for measuring pain and its associated physiological responses; thereby, lowering the intrinsic subjectivity of these experiences ( Erel and Özkan, 2017 ). Finally, in the context of the ongoing COVID-19 pandemic, infrared thermographic assessment has been proposed as an alternative to screen people to identify facial inflammatory changes suggestive of infection ( Martinez-Jimenez et al, 2021 ).…”
Section: Clinical Utilitymentioning
confidence: 99%
“…Thermal imaging has been explored in a relatively small number of studies within the field of pain research. In [18], the authors observed that facial temperature rises following a painful stimulus, indicating that thermal cameras could serve as valuable tools for pain monitoring. In [19], a pain dataset comprising RGB, thermal, and depth videos was introduced.…”
Section: Introductionmentioning
confidence: 99%